Determinants of Zakat Paying Intentions: Evidences from SMEs’ Workers in Central Java, Indonesia - Rokhman, Wahibur (UIN Sunan Kudus, 2022)
This research aims to discover the factors that influence SMEs workers in zakat paying intention in Central Java, Indonesia. Five factors are studied, including the understanding of zakat, the environment of zakat practices, the credibility of zakat institutions, the function of information, and the roles of religious leaders. This study used 394 SMEs employees who worked in various fields, and the data was processed using multiple regression. The results of this study indicate that the understanding of zakat, the environment of zakat practices, the credibility of zakat institutions, the function of information, and the roles of religious leaders significantly influence zakat paying intention among SMEs workers. The implications of this research need awareness of the managers and stakeholders of zakat institutions need to pay attention to five factors: the understanding of zakat, the environment of zakat practices, the credibility of zakat institutions, the function of information, and the roles of religious leaders because they have a significant impact on the successful development of zakat management ecosystems.